2020
DOI: 10.1155/2020/6474536
|View full text |Cite
|
Sign up to set email alerts
|

Paddy Crop and Weed Discrimination: A Multiple Classifier System Approach

Abstract: Weeds are unwanted plants that grow among crops. These weeds can significantly reduce the yield and quality of the farm output. Unfortunately, site-specific weed management is not followed in most of the cases. That is, instead of treating a field with a specific type of herbicide, the field is treated with a broadcast herbicide application. This broadcast application of the herbicide has resulted in herbicide-resistant weeds and has many ill effects on the natural environment. This has prompted many research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Successfully controlling weeds at this stage can deliver a 95% weed-free yield [23]. This is agreed with by Kamath et al [24] because the effect of weeds in this stage will be at maximum. However, if we fail to prevent weeds from spreading in the vegetative stage, they will dominate the area, leading to a lack of sufficient space, light, and nutrients to grow and develop [25].…”
Section: Controlling Weed In Paddy Fields At Different Growth Of Stagessupporting
confidence: 85%
“…Successfully controlling weeds at this stage can deliver a 95% weed-free yield [23]. This is agreed with by Kamath et al [24] because the effect of weeds in this stage will be at maximum. However, if we fail to prevent weeds from spreading in the vegetative stage, they will dominate the area, leading to a lack of sufficient space, light, and nutrients to grow and develop [25].…”
Section: Controlling Weed In Paddy Fields At Different Growth Of Stagessupporting
confidence: 85%
“…Several image processing algorithms can be used to extract distinguishing features from images or videos obtained from a scene. Numerous types of image-based features including colour [10][11][12], shape [13][14][15], texture [16][17][18], wavelet transform [19][20][21], and fusion of different features [22][23][24] have been applied to plant type identification with acceptable accuracies encouraging the further application of these image-based features for crop-weed discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…In the first, second and third years of a three-year case study, overall accuracies of 90.19%, 92.36%, and 93.8%, respectively, were achieved. Kamath et al [79] looked at how to categorize paddy crops and weeds from digital images utilizing several classifier systems developed with support vector machines (SVM) and random forest classifiers (RFs) in which the dataset included paddy plants and weeds from the seedling stage (1-leaf seedling) to the flowering stage. The results with an accuracy of 91.36% showed that multiple classifier systems were shown to outperform single classifier systems and the extracted features are good for paddy crops and weeds classification.…”
Section: Algorithms and Modelling For Weed Detection Analysismentioning
confidence: 99%